Silicon-carbon composite material and preparation method thereof, and negative plate containing silicon-carbon composite material
By oxidizing and modifying the silicon surface and sintering with a liquid carbon source, a silicon-carbon composite material with excellent interfacial binding force is prepared, which solves the problem of volume expansion and low conductivity of silicon negative electrode materials, and realizes the lithium-ion battery Stable cycle performance.
Patent Information
- Application Number
- CN202311361296.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-31
- Filing Date
- 2023-10-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-10-19
AI Technical Summary
Silicon anode materials have volume expansion effects and low conductivity problems in lithium-ion batteries, which limit their application and commercialization.
By oxidizing the silicon surface and modifying it with a silane coupling agent, a modified silicon surface is formed, and then mixed with a liquid carbon source to sinter it, a silicon-carbon composite material with excellent interfacial binding force is prepared.
This method significantly improves the bonding strength between silicon and carbon layer, improves the cyclic stability of silicon-carbon composite materials, effectively inhibits the volume expansion of silicon during lithiation, and improves the cyclic performance of the battery.
Smart Images

Figure BDA0004505807230000061
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium ion battery material preparation, and in particular to a silicon-carbon composite material and a preparation method thereof, and a negative electrode sheet containing the same. Background Art
[0002] Silicon has become an important negative electrode material for the current development of high energy density lithium-ion batteries due to its advantages such as high theoretical specific capacity, low lithiation potential, and abundant reserves. However, the large volume expansion effect and low electrical conductivity of silicon negative electrodes have limited their further application and commercialization.
[0003] In response to the problems existing in silicon materials, research at home and abroad mainly focuses on the following aspects: ① Nanometerization, by reducing the size of silicon materials to alleviate the volume effect caused by expansion, such as nanoparticles, nanowires and nanotubes; ② Porosification, using the developed pore structure inside the material to alleviate the volume expansion during charging and discharging; ③ Preparation of composite materials, combining silicon and carbon. Carbon materials have certain mechanical strength and high conductivity, which can not only alleviate the expansion of silicon materials but also increase the conductivity of composite materials.
[0004] Combining silicon with carbon materials to prepare composite materials is an effective way to solve the above problems. Coating the surface of silicon particles with carbon materials such as amorphous carbon, graphene, and carbon nanotubes can alleviate the volume expansion effect of silicon and solve problems such as low electrical conductivity of silicon materials. However, the surface of pure silicon is very inert and cannot react chemically with the coated carbon material. The two are only connected by van der Waals forces. During the battery cycle, silicon and the surface carbon layer are easily separated, affecting the cycle stability of the material. Summary of the invention
[0005] In order to solve the above technical problems, the present disclosure provides a silicon-carbon composite material and a preparation method thereof, and a negative electrode sheet containing the same.
[0006] In a first aspect, the present disclosure provides a method for preparing a silicon-carbon composite material, the preparation method comprising the following steps:
[0007] Oxidizing the silicon surface;
[0008] The oxidized silicon is mixed with a silane coupling agent to react to obtain modified silicon;
[0009] The modified silicon is mixed with a liquid carbon source and sintered to obtain the silicon-carbon composite material.
[0010] In the present disclosure, the silicon surface is oxidized to form a surface that can be modified, and then the oxidized surface is modified, thereby ensuring that the subsequent carbon coating layer has excellent bonding with the silicon core, effectively improving the interface state between silicon and carbon, and ultimately making the obtained silicon-carbon composite material have excellent cycle stability when used as the lithium negative electrode of a lithium-ion battery.
[0011] As a preferred technical solution of the present disclosure, the mass ratio of the oxidized silicon to the silane coupling agent is (30-200):1, for example, 50:1, 80:1, 100:1, 120:1, 150:1, 180:1, etc., and further preferably (50-150):1.
[0012] The present invention utilizes a silane coupling agent to modify the oxidized silicon surface. Under acidic or alkaline conditions, the silane coupling agent can hydrolyze and undergo a hydrolysis condensation reaction with the hydroxyl groups on the oxidized silicon surface, thereby realizing the introduction of the silane coupling agent. The introduction of the silane coupling agent can greatly enhance the bonding strength between the silicon and carbon layers, effectively improve the interface state between silicon and carbon, and thereby enhance the cyclic stability of the silicon-carbon composite material.
[0013] When the amount of silane coupling agent added is too small, the bonding strength between the silicon surface and the carbon layer cannot be effectively improved. When the amount of silane coupling agent added is too large, too many oxygen atoms are introduced, that is, the residual oxygen value in the obtained silicon-carbon composite material is too high, which will have a great adverse effect on the first coulomb efficiency of the lithium-ion battery using it.
[0014] As a preferred technical solution of the present disclosure, the modification is carried out under acidic conditions.
[0015] As a preferred technical solution of the present disclosure, the silane coupling agent is selected from a silane coupling agent containing an epoxy group and / or a silane coupling agent containing a hydroxyl group.
[0016] In the present disclosure, by adding a specific amount of a silane coupling agent containing epoxy groups or hydroxyl groups, uniformly distributed epoxy groups or hydroxyl groups can be formed on the silicon surface. Through the hydrogen bonding effect and electronegativity formed between the epoxy groups or hydroxyl groups and the liquid carbon source, the modified silicon can be evenly dispersed in the liquid carbon source, and a uniform liquid film can be formed on the silicon surface to achieve uniform carbon layer deposition. At the same time, the hydrogen bonds can form covalent bonds after subsequent sintering, thereby greatly improving the bonding strength between the silicon and the carbon layer.
[0017] As a preferred technical solution of the present disclosure, the silane coupling agent is selected from any one of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane or epoxypropyltrimethoxysilane, or a combination of at least two thereof.
[0018] As a preferred technical solution of the present disclosure, the silicon in step (1) is selected from any one of nano silicon particles, nano silicon wires, nano silicon sheets or porous nano silicon particles, or a combination of two or more thereof.
[0019] As a preferred technical solution of the present disclosure, the size of the silicon in step (1) is 10-500nm, for example, 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, etc., preferably 50-200nm.
[0020] The present invention can obtain a silicon-carbon composite material with extremely excellent interface stability by selecting nano-silicon of a specific size and adding a specific amount of a silane coupling agent.
[0021] As a preferred technical solution of the present disclosure, the oxidation method in step (1) includes oxidation using an oxidant.
[0022] The present invention utilizes an oxidant to oxidize the silicon surface. In an acidic environment, the alkoxy groups in the silane coupling agent are hydrolyzed into hydroxyl groups, which are hydrolyzed and condensed with the hydroxyl groups on the oxidized silicon surface, so that the silane coupling agent is bonded to the silicon surface. At the same time, the introduced silane coupling agent has a hydrogen bond effect with the liquid nitrogen source, and a covalent bond can be formed after sintering, thereby greatly improving the bonding strength between the silicon and carbon layers, improving the interface state between silicon and carbon, and improving the cycle stability of the silicon-carbon composite material.
[0023] As a preferred technical solution of the present disclosure, the oxidant is selected from hydrogen peroxide or piranha solution.
[0024] Wherein, the piranha solution is a mixture of concentrated sulfuric acid and 30% hydrogen peroxide.
[0025] As a preferred technical solution of the present disclosure, the liquid carbon source in step (3) is selected from any one of pyrrole, pyrrole, aniline, piperidine, pyrimidine, pyran or washing oil, or a combination of at least two thereof.
[0026] As a preferred technical solution of the present disclosure, the liquid carbon source is selected from any one of pyrrole, pyrrole, aniline or washing oil, or a combination of at least two thereof.
[0027] The liquid carbon source selected in the present invention can form hydrogen bonds and other effects with the modified silicon, so that the liquid carbon source can form a uniform liquid film on the silicon surface, thereby ensuring that a uniformly coated carbon layer can be formed during the subsequent sintering process; and during the sintering process, the hydrogen bonds can be converted into covalent bonds to increase the interfacial bonding force between silicon and carbon, ensuring that in the subsequent application process, the silicon and the carbon layer on the surface will not separate, thereby ensuring the cycle stability of the lithium-ion battery.
[0028] The present disclosure has no special limitation on the mixing method. Any mixing method that can evenly mix the modified silicon and the liquid carbon source is applicable to the present disclosure, preferably ultrasonic dispersion for 15-60 minutes, such as 20 minutes, 30 minutes, 40 minutes, 50 minutes, etc., and then stirring for 6-12 hours, such as 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, etc.
[0029] As a preferred technical solution of the present disclosure, the mass volume ratio of the modified silicon to the liquid carbon source in step (3) is 0.5g:(2-10)mL, for example, 0.5g:3mL, 0.5g:4mL, 0.5g:5mL, 0.5g:6mL, 0.5g:7mL, etc., and the mass volume ratio of silicon to liquid carbon source refers to the ratio between silicon and liquid carbon source, that is, 0.5g of silicon corresponds to 2-10mL of liquid carbon source.
[0030] As a preferred technical solution of the present disclosure, the mass volume ratio of the modified silicon to the liquid carbon source in step (3) is 0.5 g:(2-5) mL.
[0031] The present invention can adjust the thickness of the carbon layer of the prepared silicon-carbon composite material particles by controlling the addition amount of the liquid carbon source.
[0032] As a preferred technical solution of the present disclosure, the sintering temperature in step (3) is 900-1100°C, such as 950°C, 1000°C, 1050°C, etc.
[0033] As a preferred technical solution of the present disclosure, the sintering time in step (3) is 0.5-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, etc.
[0034] As a specific embodiment of the present disclosure, the sintering is carried out in a vertical carbonization furnace under an inert atmosphere, and the inert atmosphere is preferably N2 or Ar.
[0035] The present invention can also regulate the thickness of the carbon layer of the prepared silicon-carbon composite material particles by controlling the sintering temperature.
[0036] In a second aspect, the present disclosure provides a silicon-carbon composite material prepared by the preparation method described in the first aspect.
[0037] The silicon-carbon composite material provided by the present invention can effectively inhibit the volume expansion of silicon during the lithiation process, and has excellent interface bonding stability between silicon and carbon, and silicon-carbon separation will not occur during the application process. Therefore, when it is used as a negative electrode material for a lithium-ion battery, it can enable the battery to have stable cycle performance.
[0038] In a third aspect, the present disclosure provides an application of the silicon-carbon composite material described in the second aspect in a negative electrode material for a lithium-ion battery.
[0039] In a fourth aspect, the present disclosure provides a negative electrode sheet comprising the silicon-carbon composite material described in the second aspect.
[0040] In a fifth aspect, the present disclosure provides an electrochemical device comprising the silicon-carbon composite material described in the second aspect or the negative electrode sheet described in the fourth aspect.
[0041] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:
[0042] (1) The present invention oxidizes the silicon surface and then modifies the oxidized surface, thereby greatly improving the bonding strength between the silicon and carbon layers and effectively improving the interface state between silicon and carbon. Ultimately, when the obtained silicon-carbon composite material is used as the lithium negative electrode of a lithium-ion battery, the battery has excellent cycle stability.
[0043] (2) The preparation method of the silicon-carbon composite material provided in the present disclosure has a simple process. The silicon-carbon material is wrapped by a graphite material and has high uniformity and bonding strength. It can effectively inhibit the volume expansion of silicon during the lithiation process and is suitable for industrial production. DETAILED DESCRIPTION
[0044] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.
[0045] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.
[0046] Preparation Example 1
[0047] This preparation example provides a method for preparing a silicon-carbon composite material, comprising the following steps:
[0048] (1) Weigh 1 g of nano-silicon particles with a diameter of 100 nm, place in a three-necked flask equipped with magnetic stirring and N2 protection, add 20 mL of anhydrous ethanol, and mix well. Then add 40 mL of 30 wt% H2O2 aqueous solution, stir at 75°C for 48 h. Centrifuge at 10000 rpm for 30 min to obtain oxidized nano-silicon particles.
[0049] (2) Weigh 1g of oxidized nano-silicon particles and place them in a three-necked flask equipped with magnetic stirring and N2 protection, and add 40g of a mixed solution of deionized water and ethanol in a mass ratio of 1:3. After uniform dispersion, add concentrated hydrochloric acid to make the pH of the mixed solution ≈ 4, then add 3-glycidyloxypropyltrimethoxysilane in total 15mg to the mixed solution, stir and reflux at 70°C for 10h to allow the hydrolyzed 3-glycidyloxypropyltrimethoxysilane to react with the oxidized nano-silicon particles for dehydration condensation. After the reaction is completed, centrifuge at 10000rpm for 30min and wash with ethanol for more than 3 times. Vacuum dry at 60°C for 12h to obtain modified nano-silicon particles.
[0050] (3) 500 mg of modified nano-silicon particles were dispersed in 3 mL of pyridine, ultrasonicated for 30 min, stirred for 12 h to obtain a suspension, and the suspension was gradually sintered and carbonized at 1000 °C for 1 h in a nitrogen atmosphere at a heating rate of 10 °C / min to obtain a silicon-carbon composite material.
[0051] Preparation Example 2
[0052] This preparation example provides a method for preparing a silicon-carbon composite material, comprising the following steps:
[0053] (1) Weigh 1 g of 200 nm long nanosilicon wires, place in a three-necked flask equipped with magnetic stirring and N2 protection, add 20 mL of anhydrous ethanol, and mix well. Then add 40 mL of piranha solution, stir at 75°C for 48 h. Centrifuge at 10,000 rpm for 30 min to obtain oxidized nanosilicon wires.
[0054] (2) Weigh 1g of oxidized nanosilicon wires and place them in a three-necked flask equipped with magnetic stirring and N2 protection, and add 40g of a mixed solution of deionized water and ethanol in a mass ratio of 1:3. After uniform dispersion, add concentrated hydrochloric acid to make the pH of the mixed solution ≈ 5, then add 10mg of 3-glycidyloxypropyltriethoxysilane dropwise to the mixed solution, stir and reflux at 70°C for 10h to allow the hydrolyzed 3-glycidyloxypropyltriethoxysilane to react with the oxidized nanosilicon wires for dehydration condensation. After the reaction is completed, centrifuge at 10000rpm for 30min and wash with ethanol for more than 3 times. Vacuum dry at 60°C for 12h to obtain modified nanosilicon wires.
[0055] (3) 500 mg of modified nano-silicon wires were dispersed in 2 mL of pyrrole, ultrasonicated for 15 min, stirred for 12 h to obtain a suspension, and the suspension was gradually sintered and carbonized at 900 °C for 3 h in a nitrogen atmosphere at a heating rate of 10 °C / min to obtain a silicon-carbon composite material.
[0056] Preparation Example 3
[0057] This preparation example provides a method for preparing a silicon-carbon composite material, comprising the following steps:
[0058] (1) Weigh 1 g of a 400 nm long nano-silicon sheet and place it in a three-necked flask equipped with magnetic stirring and N2 protection, add 20 mL of anhydrous ethanol, mix well, then add 40 mL of piranha solution, stir at 75°C for 48 h. Centrifuge at 10,000 rpm for 30 min to obtain an oxidized nano-silicon sheet.
[0059] (2) Weigh 1g of oxidized nano-silicon wafers and place them in a three-necked flask equipped with magnetic stirring and N2 protection, and add 40g of a mixed solution of deionized water and ethanol in a mass ratio of 1:3. After uniform dispersion, add concentrated hydrochloric acid to make the pH of the mixed solution ≈ 3, then add a total of 5mg of epoxypropyltrimethoxysilane to the mixed solution, stir and reflux at 70°C for 10h to allow the hydrolyzed epoxypropyltrimethoxysilane to react with the oxidized nano-silicon wafers for dehydration condensation. After the reaction is completed, centrifuge at 10000rpm for 30min and wash with ethanol for more than 3 times. Vacuum dry at 60°C for 12h to obtain the modified nano-silicon wafers.
[0060] (3) 500 mg of modified nano-silicon flakes were dispersed in 5 mL of pyran, ultrasonicated for 15 min, stirred for 12 h to obtain a suspension, and the suspension was gradually sintered and carbonized at 1100 °C for 0.5 h in a nitrogen atmosphere at a heating rate of 10 °C / min to obtain a silicon-carbon composite material.
[0061] Preparation Example 4
[0062] This preparation example provides a method for preparing a silicon-carbon composite material.
[0063] The difference from Preparation Example 1 is that the liquid carbon source in step (3) is pyrimidine.
[0064] Preparation Example 5-6
[0065] This preparation example provides a method for preparing a silicon-carbon composite material.
[0066] The difference from Preparation Example 1 is that in step (3), the mass volume ratios of the modified nano-silicon particles and the liquid carbon source pyridine are 0.5 g:1 mL (Preparation Example 5) and 0.5 g:15 mL (Preparation Example 6), respectively.
[0067] Comparative Example 1-2
[0068] This comparative example provides a method for preparing a silicon-carbon composite material, which differs from Preparation Example 1 in that the mass ratios of the oxidized nano-silicon particles to the silane coupling agent 3-glycidyloxypropyltrimethoxysilane in step (2) are 10:1 (Comparative Example 1) and 300:1 (Comparative Example 2), respectively.
[0069] Comparative Example 3
[0070] This comparative example provides a method for preparing a silicon-carbon composite material, which is different from Preparation Example 1 in that the silane coupling agent in step (2) is 3-aminopropyltrimethoxysilane.
[0071] Comparative Example 4
[0072] This comparative example provides a method for preparing a silicon-carbon composite material, which is different from Preparation Example 1 in that no silane coupling agent is added in step (2).
[0073] Example
[0074] This embodiment provides a method for preparing a lithium ion battery.
[0075] (1) The silicon-carbon composite material obtained in Preparation Example 1-6 and Comparative Example 1-4, sodium carboxymethyl cellulose, and acetylene black were mixed in a mass ratio of 91:6:3, and an appropriate amount of water was added to prepare an electrode slurry, which was coated on a copper foil, and vacuum dried at 120° C. for 12 h. The copper foil coated with the electrode material was cut into a circular electrode piece with a diameter of 12 mm, and maintained at a pressure of 8 MPa for 180 s to obtain an electrode piece as a negative electrode;
[0076] (2) NCM622 with a diameter of 12 mm was used as the positive electrode, Celgard 2400 was used as the separator, 1 mol / L lithium hexafluorophosphate was used as the electrolyte, and the solvent volume ratio EC (ethylene carbonate): DEC (diethyl carbonate) was 1:1. A CR2032 button-type full cell was assembled, and the amount of electrolyte added was 50 μL. The entire battery assembly was completed in a glove box.
[0077] Performance Testing
[0078] Test: The full batteries obtained in Preparation Examples 1-8 and Comparative Examples 1-2 were subjected to charge and discharge tests. The test conditions were 500 mA / g and 100 cycles. The results are shown in Table 1:
[0079] Table 1
[0080]
[0081] It can be seen from Table 1 that the silicon-carbon composite negative electrode prepared by the oxidation modification of silicon in the present invention can enable the lithium battery to have very good capacity retention ability and cycle stability.
[0082] From the comparison between Preparation Example 1 and Preparation Example 4, it can be seen that when the liquid carbon source is pyran or pyrimidine, the cycle stability of the lithium battery is slightly poor; from the comparison between Preparation Example 1 and Preparation Examples 5-6, it can be seen that when the amount of liquid carbon source added is too little, the first reversible capacity and the first coulomb efficiency of the electrode are significantly improved, but at the same time the cycle stability is significantly reduced; and when the amount of liquid carbon source added is too much, the result is completely opposite, the first reversible capacity and the first coulomb efficiency of the electrode are reduced, but the cycle stability is improved. From the comparison between Preparation Example 1 and Comparative Examples 1-2, it can be seen that when the amount of silane coupling agent is too little, the cycle stability of the lithium battery deteriorates, and when the amount of silane coupling agent is too much, the first coulomb efficiency of the lithium battery deteriorates; from the comparison between Preparation Example 1 and Comparative Examples 3-4, it can be seen that when no silane coupling agent is added or the silane coupling agent does not contain epoxy groups or hydroxyl groups, the cycle stability of the obtained lithium battery deteriorates.
[0083] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0084] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: The preparation method comprises the following steps: Oxidizing the silicon surface; The oxidized silicon is mixed with a silane coupling agent to react to obtain modified silicon; The modified silicon is mixed with a liquid carbon source and sintered to obtain the silicon-carbon composite material.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the oxidized silicon to the silane coupling agent is (30-200):1, and more preferably (50-150):
1.
3. The preparation method according to claim 2, characterized in that: The silane coupling agent is selected from silane coupling agents with epoxy groups and / or silane coupling agents with hydroxyl groups, and is preferably selected from any one or a combination of at least two of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane or epoxypropyltrimethoxysilane.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The silicon in step (1) is selected from any one of nano silicon particles, nano silicon wires, nano silicon sheets or porous nano silicon particles or a combination of two or more thereof; And / or, the size of the silicon is 10-500 nm, preferably 50-200 nm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The oxidation method in step (1) includes oxidation using an oxidant, and preferably the oxidant is selected from hydrogen peroxide or piranha solution.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The liquid carbon source in step (3) is selected from any one or a combination of at least two of pyridine, pyrrole, aniline, piperidine, pyrimidine, pyran or washing oil, preferably selected from any one or a combination of at least two of pyrridine, pyrrole, aniline or washing oil.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The mass volume ratio of the modified silicon to the liquid carbon source in step (3) is 0.5 g:(2-10) mL, preferably 0.5 g:(2-5) mL.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The sintering temperature in step (3) is 900-1100° C. and the sintering time is 0.5-3 h.
9. The silicon-carbon composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the silicon-carbon composite material according to claim 9 in negative electrode materials for lithium-ion batteries.
11. A negative electrode sheet, characterized in that: The silicon-carbon composite material comprises the silicon-carbon composite material according to claim 9.
12. An electrochemical device, characterized in that: Contains the silicon-carbon composite material according to claim 9 or the negative electrode sheet according to claim 11.
Citation Information
Patent Citations
Silicon-carbon anode material and preparation method thereof
CN109346696A
Preparation method of silicon carbon composite material
CN109473664A
Preparation method of silicon-carbon negative electrode material of lithium battery
CN115394990A
Cited By
Preparation device suitable for carbon-based composite material of solar cell
CN224271134U